2019
DOI: 10.1103/physrevb.99.094310
|View full text |Cite
|
Sign up to set email alerts
|

Electron and phonon interactions and transport in the ultrahigh-temperature ceramic ZrC

Abstract: We have simulated the ultra-high-temperature ceramic zirconium carbide (ZrC) in order to predict electron and phonon scattering properties, including lifetimes and transport. Our predictions of heat and charge conductivity, which extend to 3000 K, are relevant to extreme temperature applications of ZrC. Mechanisms are identified on a first principles basis that considerably enhance or suppress heat transport at high temperature, including strain, anharmonic phonon renormalization and fourphonon scattering. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 55 publications
2
7
0
Order By: Relevance
“…The implications of this finding are discussed below. Interestingly, recent calculations of thermal transport in ZrC [21], a metal with rock salt structure, also show unusually weak four-phonon scattering rates and correspondingly small reductions in the phonon-phonon limited κ, consistent with our findings for the zinc blende BCN compounds.…”
Section: Four-phonon Scattering and Its Weakness In Compounds With Bo...supporting
confidence: 91%
See 2 more Smart Citations
“…The implications of this finding are discussed below. Interestingly, recent calculations of thermal transport in ZrC [21], a metal with rock salt structure, also show unusually weak four-phonon scattering rates and correspondingly small reductions in the phonon-phonon limited κ, consistent with our findings for the zinc blende BCN compounds.…”
Section: Four-phonon Scattering and Its Weakness In Compounds With Bo...supporting
confidence: 91%
“…Inclusion of four-phonon interactions in ab initio anharmonic decay rates and transport calculations is computationally challenging, and such calculations are currently performed by only a small number of groups [12][13][14][15][16][17][18][19][20][21]. Recent work has shown that for strongly anharmonic materials, it is essential to include four-phonon processes [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the thermal conductivity increases with increasing temperature. The thermal conductivity of ZrC over a wide temperature range was predicted using a single‐mode relaxation time approximation to calculate the phonon thermal conductivity, and a semi‐classical method was employed to calculate the electron thermal conductivity 20 . The total thermal conductivity was predicted to be affected by grain size, that is, larger grain size favored higher thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Ultra-high-temperature ceramics (UHTCs) make up a class of materials with high melting points of >3000 °C, , which find applications as surface coating materials for use in hypersonic flight, rocket propulsion, and space shuttles, where the friction between aerocrafts and the Earth’s atmosphere produces a tremendous amount of heat. Many transition-metal (TM) light-element compounds, such as ZrB 2 , HfB 2 , ZrC, and HfN, are good UHTC materials. Among TM borides, ZrB 2 has attracted a great deal of interest because of its superior ability to resist oxidation and its desirable mechanical and thermal properties. ZrB 2 has a high melting temperature of 3246 K, which is particularly important for its use as an UHTC material in extreme thermal environments.…”
mentioning
confidence: 99%